Noradrenaline and corticosterone memory enhancement in an object in context task in mice: mPFC activity differs due stress hormones - Morote Sánchez, Francisco Javier (2022)
Memory is an adaptive tool for survival. It is critical to remember events accurately in order to learn and interact with our surroundings. In that regard, noradrenaline and corticosterone stress hormones have been proven to improve memory but also disrupt it depending on the instant that these hormones levels rise in the brain (during information encoding, consolidating or retrieval). A less investigated aspect would be how these two stress hormones influence memory accuracy. Over time, episodic-like memories are transformed into more semantic ones, which become less dependent on the hippocampus and more dependent on cortical regions like the medial pre-frontal cortex (mPFC). The purpose of this study was to investigate the effect of yohimbine (α2-noradrenergic receptor antagonist that increases noradrenaline levels) and corticosterone in memory accuracy in a low-arousing episodic-like memory task (Object in Context), as well as related changes in mice mPFC activity. Male C57BL/6J mice were exposed to a set of two identical objects in one context for 5 min, immediately followed by exposure to another set of two identical objects in a second context. Immediately after the training they received intraperitoneal injection of either yohimbine, corticosterone or vehicle. On the 24-h retention test, mice were placed back into one of the training contexts with two objects, one copy from each set of identical objects used during training. Thus, although both objects were familiar, one of the objects had not previously been encountered in that particular context. Hence, if the animal generated an accurate memory for the association between an object and its context, it would spend significantly more time exploring the object that was not previously experienced in that context. Our findings indicated that both yohimbine and corticosterone enhanced memory accuracy. Moreover, yohimbine increased the number of c-Fos-expressing non-GABAergic cells in cingulate area 1 and prelimbic cortex of mice mPFC. By contrast, corticosterone showed no changes in GABAergic or non-GABAergic activity in the mPFC compared to vehicle. These findings suggest that glucocorticoids-related memory enhancement would be associated to a distinct brain activity that was not addressed in this study.